2021
DOI: 10.1002/jbt.22794
|View full text |Cite
|
Sign up to set email alerts
|

Rutin restrains the growth and metastasis of mouse breast cancer cells by regulating the microRNA‐129‐1‐3p‐mediated calcium signaling pathway

Abstract: Breast cancer is a common malignancy that is highly lethal. Due to the poor prognosis, more effective and efficient treatment methods are urgently needed. Rutin (RUT) is a traditional Chinese medicine reported to have a variety of pharmacological properties, including anticancer properties. However, the effects of RUT on breast cancer and its underlying molecular mechanism of action remain unclear. In the present study, we observed a significant downregulation of microRNA (miR)−129-1-3p in mouse breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“… 50 Study in breast cancer indicated that rutin restrained the growth and metastasis of mouse breast cancer cells by regulating the miRNA-129-1-3p-mediated calcium signaling pathway. 51 Among these three reports about miR-20b-5p, the last two were consistent with the current result, that is, rutin plays an anti-cancer role by regulating miRNA. However, none of the above studies emphasized the function of rutin on regulating miRNA in glioma.…”
Section: Discussionsupporting
confidence: 90%
“… 50 Study in breast cancer indicated that rutin restrained the growth and metastasis of mouse breast cancer cells by regulating the miRNA-129-1-3p-mediated calcium signaling pathway. 51 Among these three reports about miR-20b-5p, the last two were consistent with the current result, that is, rutin plays an anti-cancer role by regulating miRNA. However, none of the above studies emphasized the function of rutin on regulating miRNA in glioma.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it can be inferred that breast cancer cells need more cytoplasmic Ca 2+ for survival, and sevoflurane may increase breast cancer cells survival via modulating intracellular Ca 2+ homeostasis. Indeed, in a mouse model of breast cancer ( 72 ), regulation of the microRNA-129-1-3p-mediated calcium signaling pathway has been shown to restrain the growth of breast cancer cells. MicroRNAs are noncoding RNA molecules which participate in post-transcriptional gene regulation.…”
Section: Effects Of Sevoflurane and Propofol On Microenvironments Of Breast Cancer Cellsmentioning
confidence: 99%
“…Rutin has also been demonstrated to mitigate breast cancer cell growth via regulation of the microRNA-129-1-3p-mediated calcium signaling pathway. Overexpression of microRNA-129-1-3p mediated by rutin suppressed the proliferation, invasion, migration, and calcium overload of mouse breast cancer cells (4T1), thereby enhancing apoptosis in 4T1 cells [95]. Rutin has also been shown to have a protective effect against colorectal cancer.…”
Section: Rutinmentioning
confidence: 99%
“…colon [85], and liver [86,89] cancer, and oral squamous cell carcinoma [87] ↓ PolIII, Brf1, TNFα, iNOS, Cox2, MMP-2, MMP-9, Akt, NFκB, and c-myc Rutin Oranges, wine, and grapes ↑ Caspase-3, Caspase-9, Bax, TNF-α, GSK3-β, and p53 Neuroblastoma [91], cervical [92,94], breast [93], colorectal, lung [95,96], and prostate [97] cancer ↓ Notch-1, Hes-1, Bcl2, HPV-E6, HPV-E7, Cox2, and IL-6…”
mentioning
confidence: 99%